Microleakage testing - Gonzalez, N.A.G.; Abu Kasim, N.H.; Aziz, R.D. (1997)
Microleakage testing has been used to determine the possible clinical performance of a restorative material. Many microleakage testing materials have been developed and performed through the years. There has been no agreement as to which testing methodology would give the most accurate results. Attempts have been made to simulate the oral conditions and to give a more quantitative representation of micro leakage. The different micro leakage testing methodologies are presented in this paper.